-2(x-3)-5x=36

Simple and best practice solution for -2(x-3)-5x=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-3)-5x=36 equation:


Simplifying
-2(x + -3) + -5x = 36

Reorder the terms:
-2(-3 + x) + -5x = 36
(-3 * -2 + x * -2) + -5x = 36
(6 + -2x) + -5x = 36

Combine like terms: -2x + -5x = -7x
6 + -7x = 36

Solving
6 + -7x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -7x = 36 + -6

Combine like terms: 6 + -6 = 0
0 + -7x = 36 + -6
-7x = 36 + -6

Combine like terms: 36 + -6 = 30
-7x = 30

Divide each side by '-7'.
x = -4.285714286

Simplifying
x = -4.285714286

See similar equations:

| 25x+9y=208 | | 27a^5b^3-64a^8= | | -12w+14=8w-46 | | -13x+8x=23 | | 12+m=12 | | m-[-4]=7 | | 144x^2-16=9 | | 4x+8-x= | | 4+2(-8z-7)=(2z-9)+2 | | c^2-4c-5=0 | | -6+8z=21z-45 | | 2z+44=0 | | 5x-4+6y= | | 2(x-3)=4x+8 | | 3-4b=10b+4 | | 0=4x^4+27x^2-81 | | 85-65=2x+-7x | | x+(x+2)+(3x-5)=37 | | 8v-5=7v+12 | | 2/3+w=11/5 | | 2r+5=32r+11 | | 0=(3/2)x-5 | | 13+x=5x+1 | | 3+5(6-3)=x | | 0=(1/3)x+5 | | 12-3(y+1)=1-5(y-2) | | 2y+3z=15 | | 0=-(2/3)x+1 | | x+(x*.15)=271 | | 5x+2-5= | | 3[x+4(6-x)+24]-11=61-12x | | 2Q^2= |

Equations solver categories